Mixture Design Study of Fiber-Reinforced Self-Compacting Concrete for Prefabricated Street Light Post Structures - Wael Zatar; Tu Nguyen (Advances in Civil Engineering)
In recent years, there has been an increasing demand to produce strong precast street light posts that are aesthetically pleasing. This study presents experimental results of a considerable number of mixture designs for fabricating precast street light posts where fiber-reinforced self-compacting concrete (FRSCC) was employed. The performance of many FRSCC mixtures was evaluated in terms of their structural properties and aesthetic characteristics. A trial-and-error procedure was performed for a series of FRSCC mixtures where silica fume, fly ash, and fibers were used. Slump flow and air content tests were conducted to determine the fresh FRSCC properties, and specimens were cast to evaluate their aesthetic. Three-day and seven-day compression tests were performed to examine the FRSCC hardened properties. The amount of cement in all batches was kept constant, whereas the distributions of fine and coarse aggregates, water, and other admixtures were adjusted. The largest slump flow of 73.7 cm (29 in) was recorded, and the maximum three-day compressive strength was 43 MPa (6209 psi). Further refinement of the mixtures, which displayed the best strength and aesthetic attributes, was performed. Test results of the selected FRSCC mixtures indicated an excellent slump flow, air content, and compression values while achieving advantageous aesthetic qualities. Seven-day compressive strength of 39 MPa (5686 psi) with the air content of 4.8 percent and the slump flow of 66 cm (26 in) was recorded. The study results and the developed FRSCC mixes can be used for mass production of precast concrete street light posts in precast plants.